Are corporate governance and bank monitoring substitutes: Evidence from the perceived value of bank loans - Byers, Steven S.; Fields, L. Paige; Fraser, Donald R. (Journal of Corporate Finance, 2008)
We extend the literature regarding the importance of corporate governance and bank monitoring by examining the association between loan announcement wealth effects and the corporate governance characteristics of the borrowers. Using a sample of over 800 commercial loan announcements over a period of more than 20 years we find that loan announcements are more likely to have positive wealth effects for firms with weak internal corporate governance. However, we also find that this relation between perceived bank monitoring and board independence and incentive-based pay exists only for firms with weak external governance, specifically the market for corporate control.